Sulfonated styrenic block copolymer separator and energy storage device

JP2025037251APending Publication Date: 2025-03-17ノターク·コーポレーション
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
JP2024152123
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-05
Filing Date
2024-09-04
Publication Date
2025-03-17

Smart Images

  • Figure 2025037251000001
    Figure 2025037251000001
  • Figure 2025037251000002
    Figure 2025037251000002
  • Figure 2025037251000003
    Figure 2025037251000003
Patent Text Reader

Abstract

To provide a new styrenic block copolymer-based separator material with improved properties.SOLUTION: The disclosure relates to a functionalized sulfonated styrenic block copolymers (SSBC) in the form of a lithiated-sulfonated hydrogenated styrenic block copolymer (SO3Li-SBC). The composition is obtained by sulfonation of SBC precursor followed by neutralization of the ionic block of the sulfonated styrenic block copolymers (SSBC) by Li+ ion, thereby modifying characteristics for use as a separator in energy storage device. The separator has high ionic conductivity, a high dimensional stability / low thermal contraction and good mechanical stability, more particularly a high elongation at break.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to compositions, methods of preparation and uses of lithiated-sulfonated styrenic block copolymers. [Background technology]

[0002] Lithium-ion batteries have made great progress for use in portable electronic devices, electric vehicles and other large-scale energy storage applications. The separator is an essential component in lithium-ion batteries and directly affects the electrochemical performance, especially the safety. The separator is a key safety element to prevent the battery from short circuiting. Having a safe separator is essential for rechargeable batteries.

[0003] A separator is a porous element, usually in the form of a film, that separates the chemical reactions at the anode and cathode in a battery. Separators may be applied as a coating directly to the anode and / or cathode. A free-standing separator is one that is not applied as a coating to one of the electrodes, but instead constitutes an independent component of the battery.

[0004] Conventional separators chemically decompose in alkaline electrolytes, which limits the service life of the battery. Additionally, some conventional separators exhibit insufficient mechanical strength and poor penetration resistance due to dendrite growth. Summary of the Invention [Problem to be solved by the invention]

[0005] Improved materials are needed to solve some of the problems caused by conventional separators. New styrenic block copolymer-based separator materials with improved properties have been developed. [Means for solving the problem]

[0006] (Summary) One aspect of the present disclosure is ACBA, ACBCA, ABCBA, (ACB) n A, (ABC) n A, (ACB) n X, (ABC) n X, where n≧2 and X is a residue of a coupling agent, and mixtures thereof. Each block A is a poly(para-alkylstyrene) block having a molecular weight of 1-60 kg / mol, each block B is a hydrogenated polyisoprene block (E / P) or a hydrogenated polybutadiene block (E / B), each block B having a molecular weight of 1-10 kg / mol, Each block C is a sulfonated polystyrene-based block or a block of formula (I):

[0007] [ka] (wherein p is 1 or more, j is 1 or more, k is 0 or more, and M + is H + , Na + , K + , Li + , Cs + , Ag + , Hg + and Cu + The polymer block essentially consists of sulfonated styrene units and unsubstituted styrene units according to the present invention. Each block C has a molecular weight of 30 to 80 kg / mol. The sulfonated styrene-based block copolymer has a total molecular weight of 65 to 115 kg / mol, an ion exchange capacity of 0.5 to 3.5 meq / g, and a glass transition temperature (T) of 90 to 200° C., as measured according to ASTM 4065. g ).

[0008] The second aspect is a compound of formula (II):

[0009] [ka] (In the formula, x, y, m, n, and p are each independently 1 or more, j ≧ 1, k ≧ 0, and M + H + It is.) The present invention relates to a pentablock sulfonated styrenic block copolymer having the configuration ABCBA represented by the structure: Each block A is an endblock comprising polymerized para-methylstyrene monomer, and R1 is CH3. Each block B is composed of ethylene and butylene, or ethylene and propylene units, and each block C is composed of sulfonated styrene units and unsubstituted styrene units.

[0010] A third aspect is a film comprising a sulfonated styrenic block copolymer, the film having at least the following: a tensile stress of 6 to 20 MPa, a tensile stress of 3 to 25 MJ / m 3 Toughness, Young's modulus in dry state of 190-1100 MPa (all measurements are based on ASTM D412), DMA modulus at 80°C of 150-850 MPa (based on ASTM 4065), and elastic modulus of 5-20 kg / m 2 The present invention relates to a film characterized by having a vertical water vapor transmission rate (WVTR) (50°C / 10% relative humidity) of 100 / day.

[0011] A fourth aspect is a lithiated sulfonated styrenic block copolymer formed by neutralizing a sulfonated styrenic block copolymer with a 2 to 35 mol % aqueous solution of lithium hydroxide, and a membrane formed from the lithiated sulfonated styrenic block copolymer has a melting point of 10 -3 Scm -1 The present invention relates to a lithiated sulfonated styrenic block copolymer having an ionic conductivity at 30° C. of greater than 25% and an electrolyte pick-up at 60° C. of greater than 25% as measured by a weight gain measurement method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The following terms have the following meanings: "Consisting essentially of" means that the claimed composition contains primarily the specified material, but allows for additional ingredients that do not materially affect the novel features or function of the claimed invention, provided that, if present, the additional ingredients are in amounts of less than 30%, or less than 20%, or less than 10%.

[0013] "At least one of [a group, e.g., A, B, and C]" or "any of [a group, e.g., A, B, and C]" means a single member from the group, one or more members from the group, or a combination of members from the group. For example, at least one of A, B, and C includes, e.g., A only, B only, or C only, as well as A and B, A and C, B and C, or A, B and C, or any other combination of A, B, and C.

[0014] A list of embodiments presented as "A, B, or C" should be interpreted as including the embodiments A only, B only, C only, "A or B," "A or C," "B or C," or "A, B, or C."

[0015] "Either A, B, or C" refers to one alternative from A, B, or C, for example, A only, B only, or C only.

[0016] "Any of A, B, and C" refers to one or more options from A, B, and C, for example, A only, B only, C only, A and B, A and C, A, B, and C, etc.

[0017] As used herein, a "block" refers to a section of a polymer molecule that contains multiple identical structural units (monomers) and possesses at least one structural or compositional feature that does not occur in immediately adjacent sections (blocks). For example, a block copolymer having three blocks has the general structure (A): m (B) n (C) owhere A, B and C represent different monomers, and m, n and o represent the number of repeat units in each block. m and (C) o are in this case identified as terminal (end) blocks and have monomer compositions and / or molar masses (indicated as the number of monomer units m and o) which may be the same or different. (B) n is called the intermediate block, and the end block (A) m and (C) o The monomer composition is different from that of block (A). m , (B) n and (C) o Each of the blocks may be sequentially composed of one or more homopolymers, random copolymers or block copolymers. The intermediate block may be sequentially composed of multiple blocks to produce a block copolymer having more than three blocks, for example a pentablock copolymer. Star block copolymers are a special form of branched block copolymers and have the general formula [(A) m (B) n ] p Three or more chains of (A) are branched radially from the center (C), m and (B) n is as defined above, and p represents the number of chains, each of which is the same or different. Star block copolymers can also be used as block copolymers in the present disclosure. The structure of the block copolymer can be identified by GPC and proton nuclear magnetic resonance ("HNMR").

[0018] "Conjugated diene" refers to an organic compound containing conjugated carbon-carbon double bonds and a total of 4 to 12 carbon atoms, such as 4 to 8 carbon atoms, which may be any of 1,3-butadiene and substituted butadienes, including, but not limited to, 1,3 cyclohexadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1-phenyl-1,3-butadiene, 1,3-pentadiene, 3-butyl-1,3-octadiene, chioroprene, and piperylene, or any combination thereof. In an embodiment, the conjugated diene block comprises a mixture of butadiene and isoprene monomers. In an embodiment, 1,3-butadiene is used alone.

[0019] "Monovinylarene" or "monoalkenylarenes" or "vinyl aromatics" refer to organic compounds containing a single carbon-carbon double bond, at least one aromatic moiety, and a total of 8 to 18 carbon atoms, such as 8 to 12 carbon atoms. Examples include styrene, o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, alpha-methylstyrene, vinylnaphthalene, vinyltoluene, vinylxylene, or any mixture thereof. In embodiments, the monoalkenylarenes block comprises substantially pure monoalkenylarenes monomers. In some embodiments, styrene predominates with minor proportions (less than 10% by weight) of structurally related vinyl aromatic monomers, such as o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, alpha-methylstyrene, vinylnaphthalene, vinyltoluene, vinylxylene, or combinations thereof. In embodiments, styrene alone is used.

[0020] "Vinyl content" refers to the content of conjugated dienes that are polymerized via 1,2-addition in the case of butadiene or 3,4-addition in the case of isoprene, resulting in monosubstituted olefin or vinyl groups adjacent to the polymer backbone. Vinyl content can be measured by HNMR.

[0021] The "polystyrene content" or PSC of a block copolymer refers to the weight percent of vinyl aromatic, e.g., polystyrene, in the block copolymer, and is calculated by dividing the sum of the molecular weights of all the vinyl aromatic blocks by the total molecular weight of the block copolymer. PSC may be determined using any suitable method, such as HNMR.

[0022] "E / B" refers to a polymer block composed of randomly ordered ethylene and butylene units resulting from hydrogenation of polymerized butadiene units formed when 1,3-butadiene is polymerized by 1,2- and 1,4-addition mechanisms.

[0023] "E / P" refers to polymer blocks composed of randomly ordered ethylene and propylene units resulting from hydrogenation of polymerized isoprene units formed when isoprene is polymerized by 1,2- and 1,4-addition mechanisms.

[0024] "Coupling efficiency", expressed as % CE, is calculated using the weight percent of coupled polymer and the weight percent of uncoupled polymer. The weight percent of coupled and uncoupled polymer is determined using the output of a differential refractometer detector. The intensity of the signal at a particular elution volume is proportional to the amount of material of the molecular weight corresponding to the polystyrene standard detected in that elution volume.

[0025] "Coupling Agent" or "X" refers to coupling agents commonly used in manufacturing styrenic block copolymer SBC technology, for example, silane coupling agents such as isobutyl-trimethoxysilane, methyltrimethoxysilane, polyvinyl compounds, polyvinylarenes, di- or multi-vinylarene compounds, di- or multi-epoxides, di- or multi-isocyanates, di- or multi-alkoxysilanes, di- or multi-imines, di- or multi-aldehydes, di- or multi-ketones, alkoxytin compounds, di- or multi-halides such as silicon halides and halosilanes, mono-, di-, or multi-anhydrides, di- or multi-esters, tin tetrachloride, tetramethylorthosilicate.

[0026] "Molecular Weight" or M W M refers to the molecular weight of the styrene equivalent of a polymer block or block copolymer in kg / mol. W can be measured using gel permeation chromatography (GPC) using polystyrene calibration standards, for example, according to ASTM 5296-19. The GPC detector can be an ultraviolet or refractive index detector or a combination thereof. The chromatography is calibrated using commercially available polystyrene molecular weight standards. The M of the polymer can be measured using the GPC so calibrated. W is the molecular weight of the styrene equivalent or the apparent molecular weight. W is measured at the peak of the GPC trace and is commonly called the "peak molecular weight" of styrene equivalent, M p It is shown as:

[0027] "Electrochemical cell" refers to a "rechargeable battery" or "battery cell" that contains a positive electrode, a negative electrode, and an electrolyte between and in direct contact with the positive electrode and the negative electrode, which contains ions (e.g., Na + , Mg 2+ , Li + , K +) but electrically insulates the positive and negative electrodes. In embodiments, a rechargeable battery can include multiple positive electrodes and / or multiple negative electrodes in a single container.

[0028] "Membrane" refers to a continuous, flexible sheet or layer of material (such as a film or coating) that can act as a selective barrier, allowing some things to pass, such as molecules, ions, gases, or particles, while stopping others.

[0029] "Ion exchange capacity" or IEC refers to the total active sites or functional groups that contribute to ion exchange in a polymer. Acid-base titration methods can be used to determine the IEC, see International Journal of Hydrogen Energy, Vol. 39, No. 10, March 26, 2014, pp. 5054-5062, "Determination of the ion exchange capacity of anion-selective membrane." IEC is the reciprocal of the "equivalent weight" or EW, which is the weight of polymer required to supply 1 mole of exchangeable protons.

[0030] "Battery" refers to an energy storage system or energy device, and as used herein, "lithium ion battery" also includes batteries based on materials other than lithium, such as sodium, potassium, etc., for use in energy storage systems.

[0031] "Susceptible to sulfonation" refers to a polymer, polymer block, compound, monomer, oligomer, etc. that is susceptible or capable of reacting with sulfur-containing compounds, such as SO3, H2SO4, etc., under conditions conventionally used for sulfonation, where sulfonation is highly likely to occur to yield a sulfonated product. In embodiments, for polymer blocks that are "susceptible to sulfonation" upon sulfonation, polymer blocks having greater than 10 mol%, or greater than 20 mol%, or greater than 30 mol%, or greater than 50 mol%, or greater than 75 mol%, of sulfonic acid or sulfonate ester functional groups, the degree of sulfonation is greater than 10 mol%, or greater than 20 mol%, or greater than 30 mol%, or greater than 50 mol%, or greater than 75 mol% of the total polymer block.

[0032] By "sulfonation resistant" is meant that there is little, if any, sulfonation of the respective blocks under conditions conventionally used for sulfonation, where the blocks have less than 10 mol %, or less than 8 mol %, or less than 5 mol % sulfonic acid or sulfonate ester functional groups.

[0033] "Dry" or "dry state" refers to or describes the hydration state of a material or film that has absorbed essentially no water or only an insignificant amount of water. For example, a material or film that has only been in contact with the atmosphere is considered to be in a dry state.

[0034] "Water" refers to deionized water, tap water, distilled water, processed water, natural water, spring water, mineral water, carbonated water, hard water, or mixtures thereof.

[0035] The present disclosure relates to a separator for an energy storage device comprising, consisting essentially of, or consisting of a functionalized styrenic block copolymer in the form of a lithiated-sulfonated hydrogenated styrenic block copolymer (Li-SSBC). The copolymer is prepared by sulfonating a sulfonated styrenic block copolymer (SSBC) precursor, followed by converting the ionic block of the SSBC to Li. +It is obtained by neutralizing it with ions, thereby modifying its characteristics for use as a separator in energy storage devices.

[0036] Styrenic Block Copolymer (SBC) Precursor: The separator comprises a functionalized styrenic block copolymer derived from an SBC precursor, which is either a linear, branched, or radial block copolymer having at least one end block A and at least one interior block B and C.

[0037] Sulfonated styrenic block copolymers (SBC) have any of the following structures: triblock, tetrablock, pentablock and coupling structures. SBC precursors consist essentially of polymer blocks A, B and C, and are represented by the following structures: ACBA, ACBCA, ABCBA, (ACB) n A, (ABC) n A, (ACB) n X, (ABC) n X and mixtures thereof, where n≧2, and X is a coupling agent residue. Blocks A, B and C are defined in the following paragraphs.

[0038] Each block A is derived from a para-substituted vinyl aromatic monomer, the para-substituent being C1-C 12In an embodiment, the A block is a para-substituted styrene monomer selected from para-methylstyrene, para-ethylstyrene, para-n-propylstyrene, para-iso-propylstyrene, para-n-butylstyrene, para-sec-butylstyrene, para-iso-butylstyrene, para-t-butylstyrene, isomers of para-decylstyrene, isomers of para-dodecylstyrene, and mixtures of the above monomers. Examples of para-substituted styrene monomers include para-t-butylstyrene and para-methylstyrene, with para-t-butylstyrene being most preferred. The monomer may be a mixture of monomers depending on the particular source. The A block has a relatively higher glass transition temperature, e.g., greater than 50°C, compared to other polymer blocks in the SBC, which can result in copolymers with desirable mechanical properties and other functional properties, including morphology, making the copolymer suitable for use as a dielectric material. In embodiments, block A has a peak molecular weight from 1 to 60 kg / mol, or from 2 to 50 kg / mol, or from 5 to 40 kg / mol, or from 8 to 25 kg / mol.

[0039] In an embodiment, the A blocks constitute 30-80 wt.%, or 35-75 wt.%, or 40-70 wt.%, or 45-65 wt.%, based on the total weight of the SBC precursor.

[0040] Block B comprises a hydrogenated polymer or copolymer of conjugated dienes derived from either isoprene, butadiene, and mixtures thereof. After hydrogenation, each isoprene unit, if present, is converted to an ethylene-propylene (EP) block, and each butadiene unit, if present, is converted to an ethylene-butylene (EB) block. In an embodiment, the B block has a peak molecular weight of 1-25 kg / mol, 1-20 kg / mol, or 1-10 kg / mol, 1-9 kg / mol, or 5-8 kg / mol, or greater than 1 kg / mol, or less than 25 kg / mol, or less than 22 kg / mol, or less than 18 kg / mol, or less than 15 kg / mol, or less than 12 kg / mol, or less than 10 kg / mol, or greater than 2 kg / mol.

[0041] In an embodiment, block B is sufficiently hydrogenated such that the precursor SBC and subsequent SSBC (after sulfonation) have conjugated diene blocks of 0.15 meq / g or less than 0.10 meq / g or less than 0.05 meq / g or less than 0.03 meq / g or more than 0.0001 meq / g. The hydrogenation level of the final SSBC product as well as the hydrogenated diene polymer can be measured via UV-VIS spectrophotometry and / or 1H NMR.

[0042] In an embodiment, polymer block B has a vinyl content, prior to hydrogenation, of 8 to 85% by weight, or greater than 15% by weight, or less than 50% by weight, or 20 to 75% by weight, or 30 to 50% by weight, based on the total weight of polymerized conjugated dienes in block B. The vinyl content can be measured via 1H NMR before and after hydrogenation.

[0043] In an embodiment, the B blocks constitute up to 25 wt.%, or 5-25 wt.%, or 10-25 wt.%, or 15-25 wt.%, or 5-20 wt.%, or 5-15 wt.%, or 5-20 wt.%, based on the total weight of the SBC precursor.

[0044] In an embodiment, block C comprises segments of one or more polymerized vinyl aromatic monomers selected from unsubstituted styrene monomers. Block C is susceptible to sulfonation and constitutes 40-60 wt.%, or 45-55 wt.%, or 40-50 wt.%, based on the total weight of the SBC precursor.

[0045] In an embodiment, block C has a number average molecular weight of 30 to 80 kg / mol, or 35 to 60 kg / mol, or 40 to 60 kg / mol, or 40 to 50 kg / mol.

[0046] Sulfonated styrenic block copolymers (SSBC): SSBC are obtained by sulfonation of the above-mentioned styrenic block copolymer (SBC) precursors. SSBC have at least one sulfonic acid group, e.g. -SO3, either in acid form (e.g. -SO3H, sulfonic acid) or in salt form (e.g. -SO3Na). In an embodiment, the sulfonic acid group is in the form of a metal salt, an ammonium salt or an amine salt.

[0047] In an embodiment, the SSBC is characterized as being fully sulfonated, meaning that it has more than 10 mol% of sulfonic acid or sulfonate ester functional groups relative to the total moles of the number of sulfonated monomer units or polymer blocks ("degree of sulfonation"). In an embodiment, the SSBC has a degree of sulfonation of 1-100 mol%, or at least 10 mol%, more than 15 mol%, or more than 20 mol%, or more than 25 mol%, or more than 30 mol%, or more than 40 mol%, or more than 50 mol%, or more than 60 mol%, or more than 70 mol%, or more than 80 mol%, or more than 90 mol%, or more than 99 mol%. The degree of sulfonation can be measured by NMR.

[0048] In embodiments, the sulfonated styrenic block copolymers (SSBCs) have any of the following structures: triblock, tetrablock, pentablock, and coupling structures. SSBCs include ACBA, ACBCA, ABCBA, (ACB) n A, (ABC) n A, (ACB)n X, (ABC) n X and mixtures thereof, where n>2 and X is a coupling agent residue. At least one block is susceptible to sulfonation or other functionalization to introduce acid groups for improved hydrophilicity. In an embodiment, blocks A and B are resistant to sulfonation and block C is susceptible to sulfonation. In an embodiment, each block A is a poly(para-alkylstyrene) block and each block B is a hydrogenated polyisoprene block (E / P) or a hydrogenated polybutadiene block (E / B). In an embodiment, each block C is a sulfonated polystyrenic block or a block of formula (I):

[0049] [ka] (wherein p is 1 or more, j is 1 or more, k is 0 or more, and M + is H + , Na + , K + , Li + , Cs + , Ag + , Hg + and Cu + is selected from the group consisting of and unsubstituted styrene units.

[0050] As used herein, sulfonated styrenic block copolymers SSBC are copolymers in which M=H + It does not only refer to block copolymers having M=H + ) with an ionizable metal compound to obtain a metal salt, i.e., Na + , K + , Li + , Cs + , Ag + , Hg + and Cu + The term also refers to sulfonated styrenic block copolymers which have been further neutralized (metallated) by obtaining

[0051] In an embodiment, each block A is a poly(para-alkylstyrene), and the poly(para-substituted alkylstyrene) is derived from a para-alkylstyrene monomer selected from the group consisting of para-methylstyrene, para-ethylstyrene, para-n-propylstyrene, para-iso-propylstyrene, para-n-butylstyrene, para-sec-butylstyrene, para-iso-butylstyrene, para-t-butylstyrene, isomers of para-decylstyrene, isomers of para-dodecylstyrene, and mixtures thereof.

[0052] In an embodiment, block B is a hydrogenated polybutadiene block, and prior to hydrogenation, the polybutadiene block is derived from a conjugated diene monomer selected from the group consisting of butadiene, 2,3-dimethyl-1,3-butadiene, 1-phenyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 3-butyl-1,3-octadiene, and mixtures thereof.

[0053] In an embodiment, the SSBC comprises: Formula (II)

[0054] [ka] (In the formula, x, y, m, n, and p are each independently 1 or greater, j is 1 or greater, k is 0 or greater, and M + H + Each block A is a terminal block containing polymerized para-methylstyrene monomer, and R1 is CH3. Each block B is composed of ethylene and butylene, or ethylene and propylene units, and each block C is composed of sulfonated styrene units and unsubstituted styrene units.

[0055] In an embodiment, the SSBC has a peak molecular weight of 20-250 kg / mol, or 25-225 kg / mol, or 30-200 kg / mol, 45-175 kg / mol, or 55-150 kg / mol, or 65-120 kg / mol, or greater than 20 kg / mol or less than 250 kg / mol.

[0056] In an embodiment, the SSBC has a block B content of less than 30%, or less than 28%, or less than 24%, or less than 20%, or less than 15%, or more than 3%, or between 5 and 20%, based on the total weight of the pentablock copolymer.

[0057] In embodiments, block C is susceptible to sulfonation and constitutes 40-65% by weight, or 45-55% by weight, or 40-50% by weight, relative to the total weight of the pentablock copolymer.

[0058] In an embodiment, the weight ratio of block A to block B is from 10:1 to 1:2, or from 5:1 to 1:2, or from 4:1 to 3:1, or from 2:1 to 1:1.

[0059] In an embodiment, the ratio of sulfonated styrene units to unsubstituted styrene units in block C is 99:1-1:99 mol%, or 99.5:0.5-0.5:99.5, or 98:2-2:98 mol%, or 95:5-5:95 mol%, or 92:8-8:92 mol%, or 90:10-10:90 mol%.

[0060] In an embodiment, the SSBC has a coupling structure with the configuration of (ACB)2X, (ABC)2X, and has a coupling efficiency of 50-85%, or 55-80%, or more than 50% or less than 85%.

[0061] It should be noted that instead of sulfonating the SBC precursors described herein to obtain SSBC, other sulfonic acid group-containing polymers can be used, examples of which include perfluorosulfonic acid polymers (e.g., sulfonated tetrafluoroethylene), sulfonated polyolefins, sulfonated polyimides, sulfonated polyamides, sulfonated polyesters, polystyrene sulfonates, sulfonated styrenic block copolymers, sulfonated polysulfones such as polyethersulfones, sulfonated polyketones such as polyetheretherketones, sulfonated polyphenylene ethers, and mixtures thereof.

[0062] Neutralization of Sulfonated Styrenic Block Copolymers: In embodiments, the sulfonic acid functional groups in the C blocks of the SSBC are "neutralized" by reacting the sulfonated styrenic block copolymer with an ionizable metal compound to obtain a metal salt.

[0063] In embodiments, metal ions suitable for forming neutralized SSBC are positively charged ions of metals, preferably monovalent, divalent and trivalent ions of metals in Groups IA, IB, IIA, IIB, IIIA, IIIB and VIII of the IUPAC Periodic Table. These metal ions may be complexed or uncomplexed and may be used alone or in any mixture thereof. Suitable monovalent metal ions include Na, Na, Na+ ... + , K + , Li + , Cs + , Ag + , Hg + and Cu + Suitable divalent metal ions are Mg 2+ , Ca 2+ , Sr 2+ , B.A. 2+ , Cu 2+ , Cd 2+ , Sn 2+ , Pb 2+ , Fe 2+ , Co 2+ , Ni 2+ and Zn 2+ Suitable trivalent metal ions are Al 3+ , Sc3+ , Fe 3+ , La 3+ and Y 3+ Preferred compounds are the hydroxides, oxides, alcoholates, carboxylates, formates, acetates, methoxides, ethoxides, nitrates, carbonates and bicarbonates of the above mentioned metal ions. In an embodiment, Li + Na + is used interchangeably with

[0064] In embodiments, the neutralization reaction is carried out either: (i) by adding the metal compound directly or in a solvent to a solution of the functionalized block copolymer, followed by neutralization, precipitation, and isolation of the resulting polymer, or (ii) by melt blending the functionalized block copolymer with the metal compound. Melt blending is preferably carried out at an elevated temperature to promote uniform distribution of the metal compound and to volatilize the neutralization product.

[0065] The degree of functionalization and neutralization may be measured via known techniques, such as via infrared analysis or elemental analysis to determine the overall degree of functionality, and via titration with a strong base to determine the degree of functionality and / or the degree of neutralization (metal salt content).

[0066] In an embodiment, the SSBC is neutralized with a concentrated aqueous solution of lithium hydroxide in the range of 2-35 mol%, or greater than 2 mol%, or greater than 5 mol%, or greater than 10 mol%, or greater than 15 mol%, or greater than 20 mol%, or less than 35 mol%.

[0067] In an embodiment, the SSBC (pentablock) is neutralized with lithium hydroxide to give the compound of formula (III):

[0068] [ka] (wherein R1 is CH3, x, y, m, n and p are 1 or more, j is 1 or more, and k is 0 or more; M + Li + It is.) Neutralized SSBC (Li-SSBC) is formed.

[0069] In an embodiment, the number of groups constituting "j" in block C is in the range of 30 to 100 mol % (of block C), in which case the remainder is groups constituting "k." Block A is a poly(paramethylstyrene) block, block B is a hydrogenated polyisoprene block (E / P) or a hydrogenated polybutadiene block (E / B), and block C is a lithium-sulfonated polystyrene-based block or a polymer block essentially composed of lithium-sulfonated styrene units and styrene units.

[0070] In an embodiment, the degree of lithiation-sulfonation (LiSO3) in the neutralized lithiated sulfonated hydrogenated styrenic block copolymer (Li-SSBC) ranges from 30 to 100 mol%, or greater than 25 mol%, or greater than 30 mol%, or greater than 35 mol%, or greater than 45 mol%, or greater than 60 mol%, or greater than 75 mol%, or greater than 85 mol%, or greater than 95 mol%.

[0071] Crosslinking agents: Crosslinking agents are reactive compounds, e.g. monomers, oligomers or polymers, selected from the group consisting of acrylates, compounds having at least two vinyl groups, isocyanurates, polyisocyanates (aliphatic and / or aromatic), diisocyanates, polyesterdiols (aliphatic and / or aromatic), silanes such as alkoxysilanes or vinylsilanes, siloxanes, polyether modified siloxanes, thiols, compounds having two or more isopropenyl groups, anhydrides and mixtures thereof.

[0072] In embodiments, the crosslinker is selected from polymers / oligomers containing at least two vinyl groups, including styrene-butadiene copolymers, polybutadiene, styrene-butadiene-divinylbenzene copolymers, etc. The oligomers have at least two vinyl groups and are formed from monomers such as styrene, alpha-methylstyrene, vinyltoluene, p-methylstyrene, ethylvinylbenzene, vinylnaphthalene, and mixtures thereof.

[0073] In embodiments, the crosslinker is an aliphatic polyisocyanate or an aliphatic polyester diol.

[0074] In embodiments, the crosslinking agent is present in an amount of 0.1 to 15, or 0.5 to 12, or 1 to 10, or 2 to 8, 0.5 to 5 wt %, based on the total weight of the copolymer.

[0075] Optional Additives: In embodiments where Li-SSBC is used as the separator, the composition further comprises additives selected from the group consisting of: activators, curing agents, crosslinking agents (other than diamine based), stabilizers, neutralizing agents, thickeners, coalescing agents, slip agents, mold release agents, antiozonants, color changing pH indicators, tackifiers, film forming additives, dyes, pigments, UV stabilizers, UV absorbers, fillers, other resins, redox couples, flame retardants, viscosity modifiers, wetting agents, degassing agents, reinforcing agents, colorants, heat stabilizers, light stabilizers, lubricants, flow control agents, drip retarders, antiblocking agents, antistatic agents, processing aids, stress relief additives, binders and mixtures thereof.

[0076] In an embodiment, the composition further comprises a polymer other than the halogenated alkyl substituted SBC.

[0077] In an embodiment, the composition further comprises at least a plasticizer, a high dielectric constant solvent, or a liquid electrolyte to promote the improvement of ionic conductivity. Examples of plasticizers include bis(2-ethylhexyl)phthalate (BEHP), dibutyl phthalate (DBP), diisobutyl phthalate (DIBP), or mixtures thereof. In an embodiment, the liquid electrolyte is selected from propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), or mixtures thereof. In an embodiment, the liquid electrolyte is formed by dissolving an electrolyte (i.e., a lithium salt), such as LiPF6, LiBF4, LiClO4, LiTFSI, in a high dielectric constant solvent, which is then added to the lithiated sulfonated block copolymer.

[0078] In embodiments, the additive is used in an amount of up to 10 wt%, or 0.1-10 wt%, or 0.5-5 wt%, or 1-10 wt%, or 1-5 wt%, based on the total weight of the lithiated-sulfonated block copolymer composition.

[0079] Membranes or Films Containing SSBC / Li-SSBC: Depending on the end use, films or membranes can be formed containing SSBC copolymers or Li-SSBC copolymers. Films can be formed by known methods, for example, casting, electrospinning, extrusion, compression, coating, such as immersion, flow coating, roll coating, bar coating, spray coating, curtain, rotogravure, brushing, wire wound rod coating, pan-fed reverse roll coating, nip-feed coating, spraying, knife coating, spin coating, dip coating, slot-die coating, or ultrasonic spray coating. In an embodiment, the film is a free-standing film or is supported on a substrate, such as glass, plastic, ceramic, porcelain, etc.

[0080] In an embodiment, the film is formed directly on the electrode of the energy storage device by known methods as described above. In the case of lithium-ion batteries, the film may be formed directly on the cathode or anode. Examples include cathodes made of lithium-nickel-manganese-cobalt oxide (LiNiMnCoO2), lithium-iron-phosphate (LiFePO4), and anodes made of graphite, silicon-containing graphite, lithium metal, etc.

[0081] In an embodiment, the film is made by solvent casting. Examples of solvents include n-hexane, cyclohexane, methylene chloride, ethylene chloride, isopropyl alcohol, acetone, N,N-dimethylacetamide, 1-methyl-2-pyrrolidinone, 1,3-dioxolane, 2-methoxyethanol, dimethylformamide, benzyl alcohol, toluene, xylene, dimethylsulfoxide, and mixtures thereof. The film is then dried at room temperature to 80°C, or 30 to 70°C, or 35 to 65°C, with or without vacuum in a continuous or batch process.

[0082] In an embodiment, the film has a thickness of 0.1 to 50 μm, or 1 to 45 μm, or 5 to 40 μm, or 8 to 25 μm, or 10 to 30 μm, or 12 to 25 μm, or greater than 0.1 μm or less than 50 μm.

[0083] Crosslinking or curing by heat / radiation treatment: Depending on the application, articles obtained from compositions containing SSBC, such as films or membranes, are crosslinked either by neutralization, ionic complexation, or by curing using heat or radiation treatment. Crosslinking can be done by heat, UV radiation, gamma radiation, electron beam, or in microwaves, in the presence or absence of thermal or photoinitiators.

[0084] In an embodiment, crosslinking or curing of the film in the presence of a thermal initiator is carried out at a temperature of 40-200°C, or 45-180°C, or 50-150°C, or 55-120°C, or 60-100°C, or greater than 45°C or less than 140°C, and for a period of 1-240 minutes, or 2-220 minutes, or 5-200 minutes, or 10-150 minutes, or 15-100 minutes, or 20-60 minutes, or greater than 2 minutes or less than 60 minutes.

[0085] In embodiments, crosslinking or curing of the film is accomplished by exposing the film to E-beam or gamma radiation having a radiation dose of 10-250 kGy (kilograys), or 20-220 kGy, or 30-200 kGy, or 40-180 kGy, or 50-160 kGy, or 60-150 kGy, greater than 20 kGy, or less than 220 kGy. E-beam processing can be accomplished using electron accelerators, such as any of the following machines: electrostatic direct current (DC), electrodynamic DC, radio frequency (RF) linear accelerators (LINACS), magnetic induction LINAC, and continuous wave (CW) machines.

[0086] In embodiments, the sample or film is treated with a solvent annealing step before or after crosslinking or curing. Solvent annealing of the film can be performed by placing the film in a closed chamber equipped with a solvent reservoir for a period of 1-96 hours, or 2-72 hours, or 5-48 hours, or 12-40 hours, or more than 10 hours. In embodiments, the solvent is sprayed directly onto the film for a period of 2 seconds to 1 minute, or 5 seconds to 40 seconds, or 10 seconds to 30 seconds, or more than 2 seconds to cover the film sample with the solvent. The solvent can be any polar solvent, such as water, hexafluoroisopropanol, trifluoroethanol, ethylene glycol, methanol, ethanol, acetic acid, benzyl alcohol, 2-propanol, and mixtures thereof.

[0087] In an embodiment, the film has a thickness of 1 to 400 μm, or 2 to 200 μm, or 5 to 100 μm, or 10 to 50 μm, or 0.1 to 50 μm, or 1 to 45 μm, or greater than 0.1 μm or less than 40 μm.

[0088] In embodiments, the film is heat laminated, solvent laminated, or adhesive laminated onto a microporous support (substrate) for use in a water purification system. Non-limiting examples of microporous support substrates include polyester, polyethylene, polypropylene, polymethylpentene (PMP), polyethylene terephthalate, cellulose, cellulose nitrate, cellulose acetate, nylon, polytetrafluoroethylene, fibrous woven or nonwoven materials, etc. Alternatively, the membrane can be supported onto a commercially available membrane.

[0089] Properties of SSBC: Membranes or films comprising, consisting essentially of or consisting of SSBC are characterized by selective permeability with ion exchange capacity (IEC) properties, ionic conductivity and excellent liquid electrolyte wettability properties. The membranes / films also undergo significant swelling, e.g., at least 10-250%, or 25-250%, or more than 10%, or 35-225%, or 50-200%, or 75-175%, or less than 250%, at ambient temperature when absorbing liquid electrolyte, as measured by weight gain measurements.

[0090] In embodiments, the SSBC has an IEC, as measured by acid-base titration, of greater than 0.5 meq / g, or greater than 0.75 meq / g, or greater than 1 meq / g, or greater than 1.25 meq / g, or greater than 2.2 meq / g, or greater than 2.5 meq / g, or greater than 4.0 meq / g, or less than 4.0 meq / g, or between 1.5 and 3.5 meq / g. In embodiments, the lower ion exchange capacity membranes (1.0 meq / g) are believed to be more stable than the higher ion exchange capacity membranes (1.5 and 2.0 meq / g).

[0091] In an embodiment, the SSBC has a glass transition temperature (T ) of 90-200° C., or 90-180° C., or 95-180° C., or greater than 90° C., or greater than 95° C., or less than 200° C., as measured by dynamic mechanical analysis (DMA) according to ASTM 4065. g ).

[0092] In embodiments, films comprised of SSBC are characterized by a thickness sufficient to produce nanostructured materials for use in separator compositions, for example, films or composites for use in porous separators have a thickness of at least 0.1 μm or 0.25 μm or 0.75 μm or 1 μm or less than 1 μm, composite substrates have a thickness of 1-30 μm or 3-25 μm or 8-20 μm or greater than 1 μm or less than 50 μm, In embodiments, separators have a thickness of 1-150 μm or 3-100 μm or 5-75 μm or 8-65 μm.

[0093] The mechanical properties of the films (in the dry state) containing SSBC, measured according to the ASTM D412 standard, are given below.

[0094] In an embodiment, the film has a tensile strength of 5 to 30 MPa, or 5 to 18 MPa, or 7 to 15 MPa, or 7.5 to 14 MPa, or 8 to 12 MPa, or more than 5 MPa or less than 15 MPa, and has a tensile strength measured after 1 day (24 hours) of 3 to 10 MPa, or 3.5 to 8 MPa, or 4 to 7.5 MPa, or 4.5 to 7 MPa, or more than 3.5 MPa or less than 8 MPa.

[0095] In an embodiment, the film has a thermal conductivity of 3 to 25 MJ / m 3 Or 3.2 to 22 MJ / m 3 Or 3.5 to 20 MJ / m 3 Or 3.8 to 18 MJ / m 3 Or 4 to 15 MJ / m 3 Or 4.2 to 12 MJ / m 3 Or 4.5 to 10 MJ / m 3 or 3.5MJ / m 3 Over 15MJ / m 3 It has a toughness of less than 1000 mm.

[0096] In an embodiment, the film has a Young's modulus of 190 to 1100 MPa, or 175 to 1000 MPa, or 190 to 950 MPa, or 300 to 900 MPa, or 340 to 860 MPa, or 400 to 750 MPa, or greater than 100 MPa or less than 1100 MPa.

[0097] In an embodiment, the film has a modulus at 80° C. of 150 to 850 MPa, or 185 to 760 MPa, or 240 to 700 MPa, or 300 to 640 MPa, or greater than 150 MPa or less than 850 MPa, as measured by dynamic mechanical analysis (DMA) according to ASTM 4065.

[0098] In an embodiment, the film has a swelling percentage in water at room temperature for 24 hours that is less than 70%, or less than 90%, or less than 100%, or less than 120%, or less than 150%, or less than 200%, or less than 250%, or 3 to 70%, or 5 to 100%, or 8 to 200%, or 40 to 300%, or 50 to 250%, or 60 to 220%, or 70 to 200%, or 80 to 180%, or 100 to 160%, based on the initial total weight of the film.

[0099] In an embodiment, the film has a thickness of 1000 to 30000 g / m 2 / day or 5000~28000g / m 2 / day or 6000~25000g / m 2 / day or 7000~22000g / m 2 / day or 8000~20000g / m 2 / day or 9000~18000g / m 2 / day or 3000g / m 2 / day or more than 25,000g / m 2 In an embodiment, the film has a vertical WVTR of 1,000 to 150,000 g / m 2 / day or 5000~140000g / m 2 / day or 8000~120000g / m 2 / day or 15000~100000g / m 2 / day or 20000~80000g / m 2 / day or 15000g / m 2 / day or more than 125,000g / m 2 / day in upside down mode. WVTR measurements are in accordance with ASTM E96 / E96M at 50°C and 10% humidity in upright or upside down mode.

[0100] In embodiments, the film is durable in accelerated aging measured in water at 80° C. for up to 30 days, or more than 5 days, or more than 7 days, or more than 14 days, or less than 30 days.

[0101] In embodiments, a film containing crosslinked SSBC has a %KCl permselectivity (10:1 molar ratio) at room temperature of greater than 40% or less than 100%, or between 40 and 100%, or between 45 and 95%, or between 55 and 90%, or between 65 and 85%.

[0102] Characteristics of Li-SSBC: Li + After neutralization by the introduction of ions, the membrane or film comprising, consisting essentially of or consisting of Li-SSBC is characterized by ion exchange capacity (IEC) properties, ionic conductivity (pure polymer and saturated with liquid electrolyte), liquid electrolyte uptake, electronic conductivity, thermal stability, Li interfacial stability, lithium ion migration number and selective permeability with excellent liquid electrolyte uptake characteristics. The membrane / film also undergoes significant swelling, e.g., at least 25-250%, or more than 25%, or 35-225%, or 50-200%, or 75-175%, or less than 250%, at ambient temperature when imbibing liquid electrolyte, as measured by weight gain measurements.

[0103] In an embodiment, the film has an IEC, as measured by acid-base titration, of greater than 0.5 meq / g, or greater than 0.75 meq / g, or greater than 1 meq / g, or greater than 1.25 meq / g, or greater than 1.5 meq / g, or greater than 2.2 meq / g, or greater than 2.5 meq / g, or greater than 4.0 meq / g or less than 4.0 meq / g, or from 1.0 to 6 meq / g.

[0104] In an embodiment, the film is -9 Scm -1 Over 1.50 x 10 -9 ~2.0×10 -4 Or 2.0 x 10 -9 ~1.0×10 -4 Or 8.0 x 10 -8 ~9.0×10 -5 Or 6.0 x 10 -8 ~9.0×10 -5Or 5.0 x 10 -8 ~8.5×10 -5 , 2.5×10 -6 ~1.0×10 -3 Or 5.0 x 10 -6 ~1.5×10 -3 or 1.0×10 -5 ~2.0×10 -3 Or 2.0 x 10 -6 Over 4.0 x 10 -6 Scm -1 It has ionic conductivity of 1.0 times higher than that of pure polymer.

[0105] In an embodiment, the film has a thermal conductivity of 10.0 .mu.m at 30.degree. C. as measured by electrochemical impedance spectroscopy (EIS). -9 Scm -1 Over 1.50 x 10 -9 ~2.0×10 -4 Or 2.0 x 10 -9 ~1.0×10 -4 Or 8.0 x 10 -8 ~9.0×10 -5 Or 6.0 x 10 -8 ~9.0×10 -5 Or 5.0 x 10 -8 ~8.5×10 -5 , 2.5×10 -6 ~1.0×10 -3 Or 5.0 x 10 -6 ~1.5×10 -3 or 1.0×10 -5 ~2.0×10 -3 Or 2.0 x 10 -6 Over 4.0 x 10 -6 Scm -1 It has ionic conductivity above that of a solvent-saturated polymer.

[0106] In embodiments, the film has a liquid electrolyte pick-up of carbonate solvent (such as ethylene carbonate, dimethyl carbonate, etc.) at ambient temperature in the range of 25-250%, or greater than 25%, or 35-225%, or 50-200%, or 75-175%, or less than 250%.

[0107] In embodiments, the films have thermal stability, weight loss less than 5%, or less than 4%, or less than 2.5%, or less than 1%, as measured according to thermogravimetric analysis (20°C to 200°C ramp at 10°C / min ramp rate, isothermal TGA at 15°C for 8 hours).

[0108] In embodiments, the films have a Li interface stability of less than 10%, or less than 8%, or less than 6.5%, or less than 5%, or less than 4%, or less than 2% over time and temperature after activation cycling (i.e., less than 10% change after 100 cycles at 25° C. and 60° C.) as measured according to Lithium Symmetric Cell-Electrochemical Impedance Spectroscopy.

[0109] In embodiments, the film has a lithium ion transport number greater than 0.4, or greater than 0.5, or greater than 0.6, or greater than 0.8, or in the range of 0.4 to 1.0 according to the Bruce-Vincent method using a lithium symmetric cell.

[0110] Applications: In embodiments, the SSBC and Li-SSBC products are used in solution as flakes or as pellets for end use applications, apart from using them as films or membranes.

[0111] In embodiments, the lithiated sulfonated block copolymers (Li-SSBCs) are for use as components of energy storage devices, for example, in either a current collector, electrode, or separator (as a binder). In embodiments, the lithiated-sulfonated block copolymers are coated or deposited onto a substrate (porous separator) comprising a polyolefin. In other embodiments, a block copolymer layer is coated onto at least one side of the separator. In yet other embodiments, both sides of the separator are coated with the same or different lithiated sulfonated styrenic block copolymer compositions. EXAMPLES

[0112] The following examples are intended to be non-limiting.

[0113] The viscoelastic behavior is measured by DMA according to ASTM 4065.

[0114] Mechanical properties, including toughness in the dry state, Young's modulus, tensile strength and elongation at break, are measured according to ASTM D412.

[0115] Water vapor transmission rate (WVTR) measurements of the samples are performed according to ASTM E96 / E96M.

[0116] The degree of sulfonation of the samples is determined by potentiometric titration.

[0117] Ionic conductivity is measured by electrochemical impedance spectroscopy (EIS) using an impedance analyzer coupled with a potentiostat / galvanostat. 2 A film sample of the polyelectrolyte composition in circular shape with a size of 1 mm is placed between two stainless steel solid blocking electrodes encapsulated by a Teflon holder. For temperature-dependent ionic conductivity measurements, heat is applied to the stainless steel blocking electrodes from 20 to 100 °C by heating the tape. Impedance spectra are collected for frequencies ranging from 1 MHz to 0.1 Hz with an AC (alternating current) perturbation of 10 mV at the open circuit potential at temperatures ranging from 30 to 100 °C. The film is held at each temperature for 1 hour to reach equilibrium, which is followed by five measurements at equilibrium. The ionic conductivity is calculated using the formula: σ = L / (AR), where L is the thickness of the film and A is the cross-sectional area of ​​the blocking electrodes (approximately 1.2161 cm). 2 ), R is the resistance of the film determined by equivalent circuit regression of the Nyquist data.

[0118] The liquid electrolyte (LE) uptake of the polymer (SSBC / Celgard) membrane or film was determined by measuring the weight of a membrane piece immersed in the liquid electrolyte according to the formula:

[0119]

number

[0120] Example 1 (SSBC-1 Comparison): The sulfonated pentablock copolymer (SSBC-1) has the structure poly[tert-butylstyrene-b-(ethylene-alt-propylene)-b-(styrene-co-styrene-sulfonate)-b-(ethylene-alt-propylene)-tert-butylstyrene] (tBS-EP-sPS-EP-tBS). The tBS block has an M of 15 kg / mol. p Each EP block has an M of 10 kg / mol. p and the internal sPS block has an M of 28 kg / mol. p SSBC-1 has an IEC of 2.0 mmol / g at 10.5 wt % solids in a 1:1 (cyclohexane / heptane) non-polar solvent mixture, a molecular weight of 78 kg / mol, a glass transition temperature of 86° C., and an IEC of 7.5 kg / m 2 / day WVTR, upright (50°C / 10% RH).

[0121] Example 2 (SSBC-2): The sulfonated pentablock copolymer SSBC-2 has the structure poly[para-methylstyrene-b-(ethylene-alt-propylene)-b-(styrene-co-styrenesulfonate)-b-(ethylene-alt-propylene)-para-methylstyrene] (pMS-EP-sPS-EP-pMS). The pMS block has an M of 15 kg / mol. p Each EP block has an M of 7 kg / mol. p and the internal sPS block has an M of 42 kg / mol. pSSBC-2 has an IEC of 2.0 mmol / g at 10.5 wt % solids in a 1:1 (cyclohexane / heptane) non-polar solvent mixture, a molecular weight of 86 kg / mol, a glass transition temperature of 98° C., and an IEC of 9.5 kg / m 2 / day WVTR, upright (50°C / 10% RH).

[0122] Table 1 shows the mechanical performance of Examples 1 and 2 in the dry state.

[0123] [Table 1]

[0124] Example 3: SSBC-2 polymer (about 0.1 g) was dissolved in 50 ml of toluene / methanol (90 / 10, v / v) solution. Nitrogen was bubbled through the solution for 30 min to purge the sample of dissolved CO2. The resulting polymer solution was then treated with an excess (about 10 mol%) of concentrated aqueous lithium hydroxide solution. The product sulfonate salt of SBC (Li-SSBC) was taken and a film was prepared as described in Example 4.

[0125] Example 4: Films were prepared by first dissolving SO3LiSBC (Li-SSBC) from Example 3 to make a 2 wt % solution in either pure tetrahydrofuran (SBC-x-THF) or in an 85 / 15 v / v toluene / isopropyl alcohol mixture (SBC-x-TIPA). The solvent dielectric constant (κ) was used to assess the polarity difference between the casting solvents used: κ THF = 7.43 and kappa TIPA = 4.91. The film resulting from solution casting and subsequent solvent evaporation had a measured thickness approximately equal to 20 μm, and the substrate (composite) had a thickness of 20 μm including a 0.5 μm SO3LiSBC coating. The film was used for further processing / inspection.

[0126] A portion of the film was cast into a Teflon mold, covered to limit the rate of solvent evaporation, and left to dry for 48 hours. A portion of the resulting film was solvent vapor annealed in THF for 24 hours, followed by drying at 60 °C under vacuum for 24-48 hours. After drying, the film was immersed in an electrolyte solution for further characterization.

[0127] The ionic conductivity results of the films after neutralization with 1M LiOH solution for 24 hours are reported in Table 2 along with the electrolyte impregnation results of the film samples when immersed in electrolyte solution (1M LiPF6 in *EC / DEC v / v=1 / 1) at 25°C for various immersion periods. As shown below, the electrolyte impregnation depends on the immersion time and the ionic conductivity depends on the electrolyte impregnation. *EC / DEC refers to ethylene carbonate, diethyl carbonate, v / v refers to the volume ratio.

[0128] [Table 2]

[0129] Although the terms "comprising" and "including" have been used herein to describe various embodiments, the terms "consisting essentially of" and "consisting of" may be used in place of "comprising" and "including" to provide more specific embodiments of the disclosure, and are also disclosed.

Claims

1. A-C-B-A, A-C-B-C-A, A-B-C-B-A, (A-C-B) n A, (A-B-C) n A, (A-C-B) n X, (A-B-C) n X, and mixtures thereof [In the formula, n≧2, X is a residue of a coupling agent; Each block A is a poly(para-alkylstyrene) block having a molecular weight of 1 to 60 kg / mol; Each block B is a hydrogenated polyisoprene block (E / P) or a hydrogenated polybutadiene block (E / B), each block B having a molecular weight of 1 to 10 kg / mol; Each block C may be a sulfonated polystyrene-based block or a block of formula (I): 【Chemistry 1】 (In the formula, p is 1 or more, j is 1 or more, and k is 0 or more; M + H + , Na + , K + , Li + , Cs + , Ag + , Hg + and Cu + is selected from the group consisting of and unsubstituted styrene units according to the formula: Each block C has a molecular weight of 30 to 80 kg / mol. A sulfonated styrenic block copolymer having a general structure selected from the group consisting of: having a total molecular weight of 65 to 115 kg / mol; having an ion exchange capacity of 0.5 to 3.5 meq / g; Glass transition temperature T of 90 to 200°C measured according to ASTM 4065 g A sulfonated styrenic block copolymer having the formula:

2. Formula (II): 【Chemistry 2】 (In the formula, x, y, m, n, and p are each independently 1 or more, j ≧1, and k ≧0; M + Is H + and Each block A is an endblock comprising polymerized para-methylstyrene monomer, R 1 is CH 3 and Each block B consists of ethylene and butylene or ethylene and propylene units, Each block C consists of sulfonated styrene units and unsubstituted styrene units.

2. The sulfonated styrenic block copolymer of claim 1, which is a pentablock having an ABCB-BA configuration represented by the structure:

3. 3. A film comprising the sulfonated styrenic block copolymer of claim 2, having the following properties: Tensile stress of 6 to 20 MPa; 3-25MJ / m 3 Toughness, Young's modulus in dry state: 190-1100 MPa (All the above measurements are in accordance with ASTM D412.) DMA modulus at 80°C (according to ASTM 4065) of 150 to 850 MPa, and 5-20 kg / m 2 / day vertical water vapor transmission rate (measured at 50°C / 10% relative humidity), A film comprising at least one of the following:

4. Formula (III): 【Chemistry 3】 (In the formula, x, y, m, n, and p are each independently 1 or greater, j is 1 or greater, and k is 0 or greater; M + Li + and Each block A is an endblock comprising polymerized para-methylstyrene monomer, R 1 is CH 3 and Each block B consists of ethylene and butylene or ethylene and propylene units, Each block C consists of sulfonated styrene units and unsubstituted styrene units. is a pentablock having the configuration ABCBBA, represented by the structure The sulfonated styrenic block copolymer of claim 1 .

5. A sulfonated styrenic block copolymer formed by neutralizing the sulfonated styrenic block copolymer of claim 2 with 2 to 35 mol % aqueous lithium hydroxide solution, The membrane formed from the sulfonated styrenic block copolymer has a melting point of 100 nm as measured by electrochemical impedance spectroscopy. -3 S.C.M. -1 A sulfonated styrenic block copolymer having an ionic conductivity at 30° C. of greater than 25% and an electrolyte pick-up at 60° C. of greater than 25% as measured by weight gain measurement.

6. A film comprising the sulfonated styrenic block copolymer of any one of claims 1, 2, 4 and 5.

7. The sulfonated styrenic block copolymer according to any one of claims 1, 2, 4 and 5, wherein the weight ratio of block A to block B in the sulfonated styrenic block copolymer is in the range of 10:1 to 1:

2.

8. The sulfonated styrenic block copolymer of any one of claims 1, 2, 4 and 5, wherein block C constitutes 40 to 65 weight percent of the sulfonated styrenic block copolymer.

9. 2. The sulfonated styrenic block copolymer of claim 1, wherein the poly(para-alkylstyrene) is derived from a para-alkylstyrene monomer selected from the group consisting of para-methylstyrene, para-ethylstyrene, para-n-propylstyrene, para-iso-propylstyrene, para-n-butylstyrene, para-sec-butylstyrene, para-iso-butylstyrene, para-t-butylstyrene, isomers of para-decylstyrene, isomers of para-dodecylstyrene, and mixtures thereof.

10. 2. The sulfonated styrenic block copolymer of claim 1, wherein block B is a hydrogenated polybutadiene block, and prior to hydrogenation, the polybutadiene block is derived from a conjugated diene monomer selected from the group consisting of butadiene, 2,3-dimethyl-1,3-butadiene, 1-phenyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 3-butyl-1,3-octadiene, and mixtures thereof.

11. 1. A solid polymer electrolyte for use in an energy storage device, comprising: The electrolyte is formed by adding a sufficient amount of liquid electrolyte to the film of claim 6 for a sufficient amount of time to cause the film to swell at least 10% in volume; the liquid electrolyte comprises a lithium salt dissolved in a solvent, the lithium salt being selected from the group consisting of LiPF6, LiBF4, LiClO4, LiTFSI, and mixtures thereof, and the solvent being selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and mixtures thereof; Solid polymer electrolyte.

12. 1. A separator for use in an energy storage device, comprising: The separator is formed by applying the sulfonated styrenic block copolymer according to any one of claims 4 to 5 onto a substrate comprising a polyolefin to form a coating; The polyolefin is selected from the group consisting of modified polyolefins, polyethylene, polypropylene, polymethylpentene, and mixtures thereof, and the substrate has a thickness in the range of 3 to 100 μm; Separator.

13. The separator of claim 12, wherein the coating has a thickness of 0.1 to 25 μm.

14. 13. An energy storage device comprising the separator of claim 12.

15. An energy storage device comprising the film of claim 3.

Citation Information

Cited By

  • Supplemental fuel system for compression-ignition engine

    US12510043B2